The importance of childhood social capitals in the future well-being of children - Hosoda, Chihiro; YunFeng, Zhang; Watanabe, Junji; Maruya, Kazushi; Tabuchi, Rokuro; Hosokawa, Kenchi; Matsuhashi, Takuto (Frontiers in Psychology, 2024)
This study investigates the impact of childhood social capital (SC) and parental engagement during childhood on psychological well-being and cognitive performance in adulthood through a survey of 292 Japanese university students. By examining the dual influences of childhood SC and parental time in childhood, we aim to clarify the relationship between those early childhood factors and wellbeing and cognitive function in adulthood. Findings reveal a significant positive relationship between childhood SC and adult subjective well-being, particularly within its positive dimensions. Further, maternal involvement is linked to the cognitive abilities measured by Ravens Advanced Matrix. Hierarchical multiple linear regression analysis delineates the profound impact of childhood SC on adult well-being, highlighting the nuanced interplay between social and parental contributions to developmental trajectories. Our results emphasize the critical roles both parental and non-parental figures play in fostering social, emotional, and cognitive development from childhood through adulthood, advocating for the importance of cultivating supportive relationships throughout childhood to promote positive developmental outcomes..